Managing A Discursive Journey for Classroom Inquiry: Examination of a Teacher’s Discursive Moves - Yi̇lmaz Soysal (Journal of Science Learning, 2021)
This study presents an analysis of teacher discursive moves (TDMs) that aid students in altering their thinking and talking systems. The participants were a science who handled the immersion inquiry activities. The primary data source was the video recorded in the classroom. This video-based data was analyzed through systematic observation in two phases comprising coding and counting to reveal the mechanics of the discursive journey. Three assertions were made for the dynamics of the discursive journey. First, the teacher enacted a wide range of TDMs incorporating dialogically/monologically oriented, simplified (observe-compare-predict), and rather sophisticated moves (challenging). The challenging moves were the most featured among all analytical TDMs. Second, once higher-order categories were composed by collapsing subcategories of the displayed TDMs, the communicating-framing moves were the most prominent performed moves. Lastly, the teacher created an argumentative atmosphere in which the students had the right to evaluate and judge their classmates and teacher's utterances that modified the epistemic and social authority of the discursive journey. Finally, educational recommendations are offered in the context of teachers noticing the mechanics and dynamics of the discourse journey.